Pemikiran Ekonomi Islam Menurut Muhammad Baqir Ash-Sadr - Yuniarti, Desi; Mu’in, Rahmawati (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2024)
This article aims to explain the importance of Islamic economics in life and provide education regarding important theories from the figure of Muhammad Baqir ash-Sadr in the world of economics. This research is a qualitative study. This study includes library research. The data comes from books and research journals that discuss the topic of Muhammad Baqir As-Sadr’s economic thought. Baqir as-Sadr believes that economic problems arise because of unequal and fair distribution as a result of an economic system that allows the exploitation of the strong against the weak.